The Study of Leading Subsector and Leading Commodities of Agricultural in Anambas Islands Regency, Riau Islands Province - Marina Marina; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Agro Ekonomi, 2018)
Indonesian government is currently implementing regional development emphasizing on the characteristic and potential strength of each region. This program will be more optimal if conducted based on the introduction of the leading potential along with its use by maintaining the environmental sustainability. This research is aimed to (1) identify the basis/leading and non-basis/non-leading of agricultural sub-sector and its commodities; (2) to classify the pattern of sub-sector growth and agricultural commodities. The data used was time series consisting of secondary data from Anambas Islands Gross Regional Domestic Product (GRDP) in accordance with the basic constant price in 2010 and the production value data of agricultural commodity during 2010-2015. The data analysis by Location Quotient (LQ) and Typology Klassen method. The analysis result shows that the sub-sectors of food crops, plantation, and fishery are the basis sub-sector (LQ > 1). The commodities of wetland paddy, sweet potato, mustard, water spinach, spinach, pineapple, banana, coconut, clove, cow (cattle) and kampong chicken are the basic commodities (LQ > 1). According to the analysis of Klassen Typology, the sub-sectors of food crops and plantation crops are included in leading and fast-growing classification (rik  > riand Yik> Yi), while the commodities of wetland paddy, sweet potato, mustard, spinach, and coconut are included in the leading and fast-growing commodities.